ChemInform Abstract: One‐Pot Synthesis of Hydrophobically Modified Iminosugar C‐Alkynylglycosides: Facile Synthesis of Polyhydroxy Tetrahydroindolizines. Issue 12 (March 2016) - Senthilkumar, Soundararasu; Prasad, Sure Siva; Das, Amrita; Baskaran, Sundarababu
Abstract: The reaction of D‐ribose tosylate (I) with allyl amine followed by a Cu‐catalyzed reaction with terminal alkynes (III) gives rise to new iminosugar β‐C‐alkynylglycosides (IV), which are readily converted into novel 1‐vinyl‐tetrahydroindolizine DNA‐cross‐linking agents (V).